Expelling the “perpetrators”: ovarian cancer cells discard miR-6126 through exosomes to promote survival - Masuda, Kenta; Ahmed, Ahmed Ashour (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Ovarian cancer is the leading cause of death among gynecological malignancies. High-grade serous ovarian cancer (HGSOC), the major ovarian cancer histological type, is mostly diagnosed at a late stage and is particularly prone to metastasis to the omentum and peritoneum. The majority of HGSOCs respond well to initial treatment by taxane- and platinum-based chemotherapy. However more than half of HGSOCs relapse within 2 years and become resistant to chemotherapy. In spite of decades of translational research there has only been a small improvement in overall survival of patients with HGSOCs (1). Early detection of the disease and novel therapeutic interventions based on better understanding of the disease oncogenic drivers are required for improving clinical outcomes in HGSOCs.